Deferoxamine prevents dexamethasone-induced muscle atrophy by reducing MuRF1 and atrogin-1 - Jeong, Jae-Yeop; Son, Youngho; Kim, Youngha; Lee, Nami; Kim, Yujin; Heo, Yu Jung; Choi, Sung-E.; Choi, Jaemyung; Han, Seung Jin; Jeon, Jayoung; Kim, Hae Jin; Lee, Kwan-Woo (Frontiers in Pharmacology, 2025)
IntroductionMuscle atrophy, commonly triggered by glucocorticoids such as dexamethasone (DEX), involves increased protein degradation via the ubiquitin–proteasome system. Recent findings suggest that iron imbalance can also induce muscle atrophy. However, there have been no reports indicating that DEX causes intracellular iron imbalance leading to muscle atrophy. This study evaluated whether DEX causes iron imbalance-mediated muscle atrophy and whether deferoxamine (DFO), an iron chelator, can protect against DEX-induced muscle atrophy, exploring the underlying mechanisms in vitro and in vivo.MethodDifferentiated C2C12 myotubes were exposed to DEX, with or without DFO, to evaluate morphological changes, expression of muscle-specific ubiquitin ligases (atrogin-1 and MuRF1), and related signaling pathways via quantitative reverse transcription polymerase chain reaction, Western blotting, and immunocytochemistry. Intracellular iron accumulation was quantified using fluorescence imaging. Additionally, C57BL/6J mice were administered intraperitoneal injections of DEX, with or without DFO, every other day for 12 days. Muscle function was assessed by grip strength, and muscle mass and fiber size were measured histologically.ResultsDEX significantly induced muscle atrophy in C2C12 myotubes, elevating intracellular iron and upregulating atrogin-1 and MuRF1 via increased nuclear translocation of FOXO3a and expression of KLF15. DFO treatment prevented these effects by restoring the iron balance, enhancing AKT phosphorylation, inhibiting FOXO3a nuclear translocation, and reducing KLF15 expression. Consistently, animal experiments demonstrated that DFO administration effectively preserved grip strength, tibialis anterior muscle mass, and muscle fiber size in DEX-treated mice. Furthermore, DFO treatment restored insulin-like growth factor 1 and myostatin expression levels altered by DEX.DiscussionDFO effectively ameliorates DEX-induced muscle atrophy by modulating the AKT/FOXO3a and KLF15 signaling pathways and restoring the intracellular iron balance. These findings highlight DFO as a potential therapeutic agent for glucocorticoid-induced muscle atrophy.